‘Reconciliation is not about being cosy’: Narratives of Unchilding in Two Soweto Children’s Books - López-Ropero, Lourdes (Complutense Journal of English Studies, 2026)
While black children were at the heart of the anti-apartheid struggle in South Africa, and the iconic photograph of 12-year-old Hector Pieterson became a symbol of its brutality worldwide,  attention to children’s issues was secondary during the development of the Truth and Reconciliation Commission, which led to a deficit of acknowledgement of the system’s impact on children. This article focuses on two texts related to the student-led Soweto Uprising of 1976 and its aftermath: Adrienne Wright’s graphic novel-styled Hector: A Boy, a Protest, and the Photograph that Changed Apartheid (2019), and Nokuthula Mazibuko Msimang’s picturebook Soweto Tea Party (2022).  Drawing on Nadera Shalhoub-Kevorkian’s notion of “unchilding,” my approach will be to treat these stories as “narratives of unchilding” that expose the different ways in which black children under apartheid were deprived of the conditions that make childhood possible, while also foreground their acts of defiance. These narratives articulate representative tropes of unchilding, ranging from the construction of children as dangerous Others, to the penetration of political violence into the  most private spaces of childhood such as the home, and problematize ideas of  child victimhood to include resilience alongside vulnerability.